PENENTUAN KONDISI OPTIMUM AKTIVITAS ENZIM POLIGATAKTURONASE (PG) ENDOJINUS PULP BIJI KAKAO MENGGUNAKAN METODE PERMUKAAN RESPON - Ganda Putra, G.P. (Agrotekno; Vol. 14, No.2 Agustus 2008, 2012)
This research was conducted to determination the optimum activity of endogenous PG enzyme in cocoa pulp using response surface methodology. The results of this research had benn used as reference to develop the condition of fermentation mechanism in cocoa processing. This research was carried out by assaying the enzyme activity for 60 minutes on varying of temperature and pH. The treatment of temperature were 30, 40, 50 and 600C and pH were 3,5; 4,0; 4,5; 5,0; 5,5 respectively. Determination the optimum activity of endogenous PG enzyme in cocoa pulp using response surface methodology. The result showed that optimum condition of activity of endogenous PG enzyme was the combination of temperature 42,50C and pH 4,6 with regression model of response surface curve: Y= 750+2.27 X1 – 0,0434 X12 + 0,000260 X13 – 721 X2 + 245 X22 – 36,5 X23 + 2,01 X24, with R2= 0,929.
Keywords: optimum activity, endogenous PG enzyme, response surface methodology